2006
DOI: 10.1002/asna.200510620
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term orbital period behaviors of the neglected Algol type binaries: CC Herculis and XZ Aquilae

Abstract: Orbital period variations of two neglected Algol type binaries, CC Her and XZ Aql, are studied based on all available times of minima. In the case of CC Her, it is found that the O-C curve displays a tilted sinusoidal variation with an eccentricity of 0.54 ± 0.03 and a period of 52.4 ± 0.4 yr, which can be explained by the light-time effect due to the presence of an unseen component. The course of the orbital period change in XZ Aql appears less reliable but its O-C curve can be represented by a periodic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…Its primary component is a MS star, while the secondary is at the subgiant stage of evolution. The orbital period analysis of the system (Soydugan et al 2006b) did not show evidence of secular change of the period that can be connected with the mass transfer (cf. Hilditch 2001), although the system is semidetached.…”
Section: Search For Pulsationsmentioning
confidence: 94%
See 3 more Smart Citations
“…Its primary component is a MS star, while the secondary is at the subgiant stage of evolution. The orbital period analysis of the system (Soydugan et al 2006b) did not show evidence of secular change of the period that can be connected with the mass transfer (cf. Hilditch 2001), although the system is semidetached.…”
Section: Search For Pulsationsmentioning
confidence: 94%
“…Lanza and Rodonò (2002) and RovithisLivaniou et al (2000) proposed the relations for calculating the Q of a binary's component. Therefore, by substituting to these relations the results of the O−C diagram analysis of Soydugan et al (2006b), and the radius of the secondary component and the system's major axis (see Table 4) we found Q ∼ 7.2 × 10 50 g cm 2 , which lies between the range 10 50 < Q < 10 51 and could potentially implicate the cyclic period modulation of the system (Lanza and Rodonò 2002). Although we found that the secondary component is magnetically active (see Sect.…”
Section: Search For Pulsationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The LITE equation as described as a time delay, which is given by Irwin (1959) is commonly used for the analysis of changes in orbital period (e.g. Soydugan et al 2003Soydugan et al , 2006Zasche et al 2014). The parameters derived from the analysis applying the quadratic term and LITE to O-C data are reported in Table 5.…”
Section: Orbital Period Variationsmentioning
confidence: 99%